Perceptions of bureaucracies in Ecuador about the endogenous factors that influence the performance of public servants in Cuenca, 2019-2021 - Riera Robles, Gabriela Estefanía; De la Garza Montemayor, Daniel Javier (Estado, Gobierno y Gestión Pública, 2021)
In this article, we seek to examine the perspective of street bureaucracies in Ecuador, on the management model based on Open Government. For this purpose, endogenous dimensions to public administration were considered, such as administrative feasibility, collaboration and innovation, and legal feasibility. To evaluate the implementation of the model, structured interviews were carried out with public servants who were selected for their professional experience, as well as for the responsibility they exercisedduring the years 2019 and 2020.The study concludes that one of the most important criteria is the training and aptitude of public officials.